Strategies for combating antibiotic resistance: seeking new solutions - Vashchyk, Yevheniia; Tsimerman, Olesya; Ladohubets, Olena; Duchenko, Kateryna; Zakhariev, Andriy; Shapovalova, Olga (ScienceRise: Biological Science, 2025)
The aim: study of innovative world strategies of fight with antibiotic resistance. Materials and methods. The study was conducted by analyzing available scientific literature, open sources in the databases Google Scholar, PubMed, Clarivate, Web of Science, Scopus, etc., as well as the results of our own research. The results. The Global Action Plan on Antimicrobial Resistance, developed by WHO, was approved in 2015, and in 2023, it was found that 134 out of 194 countries, including Ukraine, which is 69% of the world’s countries, had officially adopted national action plans. However, today there are difficulties in effective communication between all countries and the full implementation of the Global Plan, national action plans due to the fact that developing countries have limited resources for the necessary measures. Antibiotic-resistant bacteria and antibiotic resistance genes are extremely dangerous for human health, which can be compared to a time bomb. Therefore, the fight against antimicrobial resistance requires the consolidation of the work of various industries and should be based on the following areas: the development of partnership programs to optimize the use of antibiotics; the introduction of effective intelligent control and prevention systems; financing programs for the development of new antimicrobial drugs and alternative treatment methods; increased control and intensification of monitoring of the development and spread of resistant microorganisms. Conclusions. The main reservoirs of antibiotic-resistant bacteria and resistance genes are livestock farms, hospitals, sewage treatment plants and agricultural lands, so the strategy to combat antibiotic resistance should be based primarily on One Health approaches. The solutions proposed by scientists to combat antimicrobial resistance - new antibiotics; pro-, pre-, symbiotic drugs; enzymes for the destruction of biofilms, adhesion inhibitors and associated therapy with adjuvants or phages - have a positive effect, but currently still require regulatory intervention for large-scale use. Effective control of antimicrobial resistance requires investment, training of specialists, raising public awareness, comprehensive policies and regulatory systems that ensure a balance between public health protection and the appropriate use of antibiotics